Dynamic Capabilities: A Case Study in Application Jaga Kendari - Indah Cahyani; Alwi Alwi; Nurdin Nara (Institute of Computer Science (IOCS), 2022)
The concept of dynamic capabilities introduced by Teece and Pisano in 1994 emphasizes the key role of strategic management in adapting, integrating, and reconfiguring internal and external organizational skills, resources and functional competencies appropriately to a changing environment. Various problems that often occur in the public sector in Indonesia are due to environmental changes such as the emergence of the Covid-19 pandemic and the competition between the public sector itself in providing excellent service. This study uses a qualitative method with a descriptive approach. The results showed that the dynamic capabilities applied were based on three things, namely Organizational and Managerial Processes, Positions and Path Dependencies. Based on these three points, the Kendari City Population and Civil Registry Office has proven to have carried out its duties and made every effort possible by utilizing technology and adopting innovations in the face of a rapidly changing environment. However, in implementing the Jaga Kendari application, people complain starting from the network that does not support, inadequate facilities and infrastructure and there are still many people who are still unfamiliar with the application of the internet system because of the lack of effective socialization to the community.